ANALISIS RETURN SAHAM SEBELUM DAN SESUDAH PENGUMUMAN RIGHT ISSUE PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (Tahun 2010 - 2014) - Parmitasari, Rika Dwi Ayu; Kandi, Rama (Jurnal Minds: Manajemen Ide dan Inspirasi, 2016)
This study aimed to analyze the differences in stock returns before and after the announcement of the rights issue. The announcement of the rights issue is one of information needed by investors as a basis for making investment decisions. By because it will be tested whether the announcement of the rights issue have information content that is strong enough to make the market react. Whether there is a market reaction will be indicated by the difference in stock returns. The population in this study is a banking company listed on the Indonesia Stock Exchange that perform announcement right issue in 2010 to 2014, with a sample of 26 banking. The sampling method is purposive sampling method. This study is event study. Hypothesis testing is done with a simple t- test paired t-test because they normally distributed data. These results indicate that there are significant differences between stock returns before and after the announcement of the rights issue in the banking company rights issue in 2010 - 2014. The period specified study period ie 11 days can reflect the state of the market that reacts based on the content of the information from the announcement. The market reaction indicated by the price change and stock returns by events there.